Natural and anthropogenic controls on heavy metal distribution in East China Sea sediments - Li, Jinduo (Frontiers in Marine Science, 2025)
Understanding the distribution and sources of heavy metals in marine sediments is critical for assessing environmental quality and sedimentary processes. The East China Sea (ECS) shelf, influenced by multiple terrestrial and oceanic inputs, provides an important setting to evaluate heavy metal behavior in sandy sediments. In August 2023, surface and core sediment samples were collected from the ECS shelf. Grain size composition, organic matter content, and heavy metal concentrations (Cr, Cu, Zn, Pb, Hg, As, Cd) were analyzed to determine their spatial distribution, controlling factors, and environmental implications. The average concentrations of Cr, Cu, Zn, Pb, Hg, As, and Cd in surface sediments were 51.85, 16.95, 66.93, 21.32, 0.025, 5.58, and 0.083 mg/kg, respectively. Higher concentrations were recorded in the western nearshore and northeastern shelf, while lower and more uniform values occurred across the central and southern regions. Core sediments showed similar concentration ranges to surface samples. Sediment grain size and organic matter were the primary controls on metal distribution. Statistical analyses and enrichment coefficients indicated that most heavy metals derived from terrestrial detrital sources were transported with fine-grained components. However, Hg, Cd, Pb, and As showed signs of anthropogenic influence. Vertically, Cr, Cu, Zn, Pb, and Cd exhibited no significant trends, Hg displayed notable variability, and As was elevated in northern sediments compared to southern counterparts. The ECS sandy sediments remain relatively clean with low levels of heavy metal contamination. Nevertheless, sediment reworking and modern depositional processes have redistributed metals, particularly those influenced by human activities. The findings highlight the combined role of natural grain size control and anthropogenic inputs in shaping heavy metal patterns, contributing to understanding regional sedimentary processes and environmental quality.